Chitooligosaccharides as novel ingredients of fermented foods - Vela Gurovic, M. S. (2015)
Chitooligosaccharides (COSs) have been clinically evaluated for their immunostimulating effects after oral intake. Similar to dietary supplements, prebiotics and biopreservatives, these water-soluble bioactives are easily incorporated into dairy products and beverages. Notwithstanding, the use of COS in fermented foods would be limited by its antimicrobial properties. In order to study the interaction with yoghurts as a model of fermented food, the effects of COS on chemical composition, viability, morphology and metabolism of lactic acid bacteria, fatty acid profiles and conjugated linoleic acid (CLA) were assessed over 28 days and after chemical digestion. There were no significant differences between the nutritional composition of controls and yoghurts supplemented with concentrations up to 0.1% w/w of COS. However, the acidification of milk decreased at 0.5% (p < 0.05) and the formation of yoghurt failed at 3.0%, without affecting viable counts. Lipid hydrolysis of yoghurts supplemented with 0.1% COS was not affected by chemical digestion. No significant differences were found between CLA percentages of controls and supplemented yoghurts after digestion. Although the nutritional composition, fatty acids and viable counts were not significantly modified after COS supplementation, the present study shows that COS diminishes bacterial acidification at concentrations higher than 0.1%, thus limiting the amounts that could be added to yoghurt.